Agroecological Investment Cases in Kenya: Investment cases for selected agroecological business enterprises in Kenya - Chege, Christine Kiria; Wanyama, Rosina; Onyango, Kevin; Bolo, Peter; Ndiwa, Aurillia M (2024)
Investing in agroecology is key in supporting agroecological food system transformationThe Agroecology Initiative (AE-I) partnered with the CGIAR Food System Accelerator (CFSA) program to provide technical support to agroecological business enterprises to scale selected innovations in Kenya and Zimbabwe. In Kenya, three business enterprises were selected to participate in the program, two input-based enterprises and one output-based enterprise. The input-based enterprises specialize in production of organic input and selling them to farmers in the fruit and vegetable value chains in Kiambu and Makueni Counties in Kenya, while the output-based enterprise procures fruits from different regions in Kenya and processes them for local and export market (mainly dry fruits). The output-based company is also engaged in organic waste management. This report therefore provides an in-depth description of three investment cases proposed for agroecological transition in Kenya, one from each enterprise. Each case shows the business model for the enterprise, the model’s strengths, weaknesses, opportunities and threats, level of integration of agroecological principles, selected interventions for agroecological transitions, estimated cost of scaling in the short-run, results from a cost-benefit analysis (CBA) of agroecological transitions, and a brief description of the pitching event designed to attract potential long-term investors. Key tools used for assessment include the Business Model Canvas (BMC) of the LINK methodology, and Biovision’s Business Agroecology Criteria Tool (B-ACT), Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis and Cost benefit Analysis (CBA). The results show that the three enterprises have over 50% AE score, with input-based enterprises having higher scores (63.5%-69.3%) than the output-based enterprise (52.5%). Results from the CBA show that higher investments are likely to take longer to observe returns but are more profitable than smaller investments that take a shorter time with lower returns. Learnings from these cases collectively show that there is a huge potential for agroecological investment at farm and off-farm level, and private enterprises could play a significant role in scaling promising innovations. This calls for increased investment in agroecological innovations and partnerships with private enterprises for a larger impact.